EFFECT OF CORPORATE FINANCIAL PERFORMANCE USING RATIO ANALYSIS AND FINANCIAL ANALYSIS BASED ON VALUE ADDED TOWARD STOCK RETURN IN SECTOR COMPANY OF CONSUMER GOOD ON THE IDX PERIOD 2004 – 2008 - Rudianto, Dudi (Business and Management Review, 2012)
This study was conducted to determine the condition of  company's financial performance using financial ratios and financial analysis based on value added and the impact on stock returns consumer goods sector company listed on the IDX period 2004-2008. From the research conducted, the result that the overall financial performance of the company measured by using two measures of financial performance that shows good condition with an increasing trend. The deteriorating financial condition in 2008 was as a result of the global financial crisis that also adversely affect the market perception of the company's stock performance in the sector. Simultaneously, a significant difference between the financial ratios of the company (X1) and financial analysis based value added (X2) as a measure of financial performance of the company's stock return (Y) in the consumer goods sub-sector company listed on the IDX period 2004-2008, with a coefficient of determination of 60%. But partially only variable X1 which financial ratios covering CR, DAR, NPM and PBV has a significant relationship to stock returns and have a greater influence than financial analysis based value added (which includes EVA and MVA). Keywords: Financial performance, financial ratios, financial analysis based on value added and stock returns REFERENCES Agus Sartono dan Kusdhianto Setiawan, (1999), Adakah Pengaruh EVA Terhadap Nilai Perusahaan dan Kemakmuran Pemegang Saham Pada Perusahaan Publik?. Jurnal Ekonomi dan Bisnis Indonesia, Vol.14, No.4, hal. 124-136. Amin Widjaya Tunggal, (2001), Memahami Konsep Economic Value Added dan Value-Based Management. Penerbit Harvindo, Jakarta. Barker, Richard G., (1999). Survey and Market-based Evidence of Industry dependence in Analysts Preferences Between the Dividend Yield and Price-ernings Ratio Valuation Models. Journal of Finance & Accounting 26, (3) & (4), 0306-686X: 393-416. Bacidore, Jeffery M., Boquist, John A., Milbourn, Todd., and Thakor, Anjan V, (1997), The search for the best finance performance measure. Financial Analyst Journal, May-June: 11-20. Brigham, Eugene F. and Houston, Joel F. (2004). 10 th ed. Foundamentals of Financial Management. Thomson. South-Western. Dermawan Wibisono, 2000. Riset Bisnis. Edisi Pertama. Penerbit BPFE. Yogyakarta. Dewanto, (1988). Pengaruh EVA Terhadap Harga Saham. Jurnal Ekonomi dan Bisnis Indonesia, Vol. 14, No. 4: 124-126. Francis, Jack C. (1988), Management of Investment, 2nd ed., International Editions Financial Series, Singapore: McGraw Hill. Ferson, Wayne E.: and Harvey, Campbel. R., (1996). Fundamental Determinants of National Equity Market Returns: A Perspective on Country Risk and Asset Pricing. Journal of Banking and Finance, Fourtcoming. Ghozali, Imam. (2001). Aplikasi Analisis Multivariance dengan Program SPSS. Badan Penerbit Undip, Semarang. Gitman, Lawrence J. (2003), Principles of Managerial Finance, 10th ed., International Editions Financial Series, Boston: Addison-Wesley. Gujarati, Damodar N. (2003). Basic Econometric. Mc Graw Hill. International Edition Financial Series. Singapore. Hair, Joseph F., Anderson, Rolph E., Tatham, Ronal L., and Black, William C., (1998). Multivariate Data Analysis. 15th ed. Prentice-Hall, International, Inc. Hartono, Jogiyanto dan Chendrawati, (1999). ROA dan EVA: A Comparative Empirical Study. Gajah Mada International Journal of Business, Vol. 1, No.1, May, 45-49. Husnan, Saud, Hanafi, Mamduh M. dan Wibowo, Amin (1996). Dampak Laporan Keuangan terhadap Kegiatan Perdagangan saham dan Variabilitas Tingkat Keuntungan. Kelola, No. 11, Vol. V: 111-146. Jones, Charles P. (1996). Investments. Fifth Edition. John Wiley & Sons Inc. New York. Lee CM, (1996). Measuring Health, CA Magazine, April. Machfoed Mas’ud, (1994), Financial Ratio Analysis and The Prediction of Earning Changes in Indonesia, Kelola, No. 7/III/1994: 114-134. Rina Trisnawati, (1999). Pengaruh Informasi Prospektus pada Return Saham di Pasar Modal. Simposium Nasional Akuntansi II dan Rapat Anggota II. Ikatan Akuntansi Indonesia, Kompartement Akuntansi Pendidikan, 24-25 September: 1-3. Robbert Ang, (1997). Buku Pintar: Pasar Modal Indonesia. Mediasoft, Indonesia. Rousana M, (1997). Manfaat EVA Untuk Menilai Perusahaan di Pasar Modal di Indonesia. Usahawan, No. 4, Th. XXVI, April, 1997. Singgih Santosa, (1999). SPSS (Statistical Product and Service Solution). Penerbit PT. Alex Media Komputindo-Kelompok Gramedia, Jakarta. Syahib Natarsyah, (2000), “Analisis Pengaruh Beberapa Faktor Fundamental dan Risiko Sistematik terhadap Harga Saham (Kasus Industri Barang Konsumsi yang Go Publik di Pasar Modal Indonesia)”, Jurnal Ekonomi dan Bisnis Indonesia, Vol. 15, No. 3: 294-312. Stoner, James A.F., R. Edward Freeman, and Daniel R.Gilbert (1995), Management, 6th ed., New Jersey: Englewood Cliffs. Teguh Prasetyo (2000), Analisis Rasio Keuangan dan Nilai Kapitalisasi Pasar sebagai Prediksi Harga Saham di BEJ pada Periode Bullish dan Bearish, Simposium Nasional Akuntansi III, Ikatan Akuntasi Indonesia, Kompartemen Akuntan Pendidik, Agustus: 652-695. Triyono dan Jogiyanto HM, (2000), Hubungan Kandungan Informasi Arus Kas, Komponen Arus Kas, dan Laba Akuntansi dengan Harga atau Return Saham, Jurnal Riset Akuntansi Indonesia, Vol. 3, No. 1, Januari: 54-68.